Technology change management imperatives for developing economies - Sharif, Nawaz (Technological forecasting and social change)
This paper begins with the well-accepted premise that technological progress provides the foundation for economic prosperity. And, because most developing countries are lagging behind due to technological underdevelopment, a judicious management of the technological advancement process deserves serious attention. Keeping these in mind and also taking stock of the current global perspective for developing economies, what problems and issues will have to be dealt with, and what bottlenecks will have to be removed are presented first. The middle portion of the paper then deals with a brief dissection of the vital dimensions of the required technological change management system for practitioners and policymakers in these countries. The third and the last part presents some observations/comments regarding the attitudinal, organizational and institutional changes that could help in achieving the aspired technology-led economic miracle.